The Influence of Perception and Religiosity on Consumer Behaviour: An Perspective of Consumption in Al-Qur'an - Devid Frastiawan Amir Sup; Mohamad Zaenal Arifin; Ziad Abdurrahman Azzahid; Ulfatun Wahidatun Nisa (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: This research aims to identify the influence between perception and religiosity on consumer behaviour at Otsmani Coffee Solo, the identify whether perception and religiosity have a significant influence on consumer behaviour patterns at Otsmani Coffee Methods: This research used quantitative research approach. This research is included in survey research. This research used a quantitative analysis approach that adopts Partial Least Square (PLS) using SmartPLS version 4.1.9.4 as an analysis tool. Results: This research found that customer perception and religiosity have a significant influence on consumer behaviour to buy at Otsmani Coffee Solo. This research confirmed the idea that attitudes, subjective norms, and behavioral control influence customers intentions and decisions to purchase products. In addition, Otsmani Coffee Solo competitiveness in the market is influenced by variables such as product suitability, brand identity, customer loyalty, emotional attachment, and difference from competitors. Conclusion and suggestion: The results suggest that value-based and identity-based marketing strategies that match consumer preferences and beliefs are essential for consistently increasing customer attraction and loyalty. Furthermore, it is important for consumers to adhere to the concept of consumption in Al-Quran: consuming what is halal and thayyib; being proportionate, not being excessive (israf) and not being stingy (bakhil); and always acknowledging the blessings of Allah SWT.